Monetary Policy and the Informal Sector: an assessment - Bala-Keffi, Ladi Raulatu (Nigeria National Institute for Policy and Strategic Studies, 2022)
The study assessed the impact of monetary policy on the informal economy. The specific objectives include to assess the impact of monetary policy instruments on the informal economy in Nigeria; evaluate the effectiveness of the interest rate and credit channels of monetary policy in influencing the informal economy; and test for the presence of assymetry between monetary policy and the informal sector.
An individual project submitted to the National Institute for Policy and Strategic Studies, Kuru, in partial fulfillment of the requirement for the award of Member of the National Institute (mni)
osc 25/04/23
Arch.
Keywords: Monetary policy; Nigeria